â€˜ANXIETASâ€™ TOKOH-TOKOH UTAMA DALAM NOVEL THE GREAT GATSBY KARYA F. SCOTT FITZGERALD - WANGKANUSA, MARDIANTO NATANAEL (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This skripsi entitled â€œAnxiety of the Major Characters in the Novel The Great Gatsby by F. Scott Fitzgeraldâ€is intended to be one of the requirement to accomplish the â€œSarjanaâ€ at the Faculty of Humanities Manado. The aims of this analysis are to analyze and classify the kind of â€˜anxietyâ€™ of the major characters in the novel The Great Gatsby. The interactions among the major characters, the characterization of the major characters, including the identification and category of â€˜anxietyâ€™ are described. In terms of methodology, the combination of two approaches applied namely the intrinsic as well as the extrinsic ones. The concept of â€˜anxietyâ€™ and its categories including â€˜charactersâ€™, are two concepts representing the extrinsic and the extrinsic ones.Â  The psychological theory about â€˜anxietyâ€™ by Freud in Minderop (2010) and Davison, Neale and Kring (2012) and also a paradigm by Roberts (1983) are used, to be completed by a descriptive analysis. The data are collected according to â€˜content analysisâ€™ method. The results of this research show that all major characters tend to have â€˜anxiety disorderâ€™ reaching this level of abnormality. Nick Carraway has â€˜objective anxietyâ€™ and categorized in phobia disorder and generalized anxiety disorder, Jay Gatsby has neurotic anxiety and categorized in obsessive compulsive disorder.